Understanding the genetic relationship between key effectors of DNA interstrand crosslink repair - Brolih, S (2016)
With each cell division, our whole genome is duplicated in an error-free and controlled manner. Failure to do so leads to genomic instability. DNA interstrand crosslinks (ICLs) are particularly toxic DNA lesions as when left unrepaired, they are able to block replication producing devastating health conditions such as the genetic syndrome Fanconi Anemia (FA) that predisposes its patients to cancer. The repair of ICLs is thought to be initiated by the concerted action of multiple nucleases, some of which are defective in FA patients. In particular, the 5'-3' exonuclease SNM1A works in a common pathway with the heterodimeric endonuclease XPF (ERCC4/FANCQ)–ERCC1 during replication-associated ICL repair. We wish to investigate the role of the less well-characterised nuclease FAN1. It has previously been shown that cells deficient in key nucleases XPF-ERCC1, SNM1A and FAN1 all show increased sensitivity to widely used crosslinking anticancer drugs, underlining the clinical importance of exemplifying the exact mechanism of ICL repair. The project both focuses on a biochemical and cellular characterization of the nuclease FAN1. Through nuclease assays on radioactively end-labelled synthetic DNA substrates mimicking replication fork intermediates, FAN1 was characterised as a 5’ flap endonuclease as well as a 5' to 3' exonuclease. On a cellular level, a functional redundancy between the two repair nucleases FAN1 and SNM1A was identified. In order to better understand the genetic relationship between FAN1 and the key exonuclease XPF-ERCC1, I generated a XPF -/- human cell line using the CRISPR/Cas9 gene-editing technology. In future, this tool will enable us to better understand the genetic relationship between XPF-ERCC1 and FAN1 leading to a more complete understanding of ICL repair. Altogether, the project offers an overview of the biochemical and genetic relationship between key nucleases of the DNA ICL repair and can offer interesting mechanistic insight in ICL incision, unhooking and repair, potentially identifying new therapeutic targets.